Organizing Informal Workers Globally: Comparing a Global Union Federation and a Global Informal Worker Organization Network - Tilly, Chris (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
SummaryWith economic globalization and with the precarization and informalization of work, efforts have increased to build global labour alliances among formal workers on the one hand and to organize informal workers on the other. These two endeavours overlap considerably. Global labour organizations have taken on a growing role in organizing and advocating for informal workers. I explore this overlap by comparing two global labour federations: one arising from heterogeneous networks of informal workers—the International Domestic Workers Federation (IDWF)—and a longstanding one of formal employees that has increasingly attempted to include informal workers—the Building and Wood Workers International (BWI).For both cases, I draw on five sources: secondary literature; archival material from the two federations; seven semi-structured interviews with experts on and members of these federations, plus a meeting with a small group of BWI leaders; and observations of several IDWF and BWI events.This comparison yields two striking findings. First, despite contrasting environments and historical legacies, the two federations show much convergence in strategy. Second, they clearly differ in their degree of adherence to the standard trade union model, as a result of differences in assets and challenges. The BWI is strongly wedded to the conventional model and struggles to reach informal workers, while enjoying a robust inflow of membership dues. The IDWF is committed to welcoming a variety of organizations and readily mobilizes informal workers, while suffering from an anemic inflow of membership dues. These challenges must be met not just for the survival of the BWI and the IDWF but also for the prospect of organizing globally to defend informal and precarious workers.AbstractWith economic globalization and with the precarization and informalization of work, efforts have increased to build global labour alliances among formal workers on the one hand and to organize informal workers on the other. These two endeavours overlap considerably. Global labor organizations have taken on a growing role in organizing and advocating for informal workers. I explore this overlap by comparing two global labour federations: one arising from heterogeneous networks of informal workers—the International Domestic Workers Federation—and a longstanding one of formal employees that has increasingly attempted to include informal workers—the Building and Wood Workers International. The contrast reveals similarities, divergences and trade-offs, with important implications for the future potential for building global organizations of informal workers.